Looney tunes platinum collection. (Warner Home Video, 2012)
Make way for Looney Tunes Platinum Collection Volume 2 with 50 animated theatrical shorts remastered in stellar hi-def Blu-ray in all their stellar silliness. Selections include the core characters, such as Bugs Bunny, Daffy Duck, Porky Pig, Tweety and Sylvester, Pepé Le Pew and Foghorn Leghorn. While Disc Two offers one-shot classics, and disc three serves up great fun and insider info with its wild array of bonus programs saluting legendary animators and historical gems.